Papua prevents stunting: Infant and child feeding training (PMBA) for cadres as an effort of nutrition education to mothers who have never attended school - Manossoh, Sindy Ameida Penina (BKM Public Health and Community Medicine, 2021)
Objective: This study examines the ability of cadres to approach to provide education to mothers who never attended school either in the form of information delivery and demonstration of infant and child feeding. Content: Stunting is one of the health issues that is an important concern for the government because it concerns the nutritional problems of toddlers which are the highest at this time, in early 2021, the Indonesian government is targeting the Stunting rate to drop to 14% in 2024. In Papua, Stunting included in the top three health issues with a number 30% in 2020, where this figure is still very far from the target for reducing Stunting Nationally. Prevention efforts are hampered by the lack of health cadres, besides the lack of knowledge and ability to carry and distribute information from cadres to parents about how to properly feed children, especially to mothers who have never been to school about Stunting is also one of the contributing factors. Based on the explanation of the problem, this is the reason why Stunting in Papua requires treatment and prevention as soon as possible. As one of the efforts to prevent stunting, especially for mothers who have never attended school and do not have knowledge of good and correct feeding practices to children according to age, the Infant and Child Feeding Training (PMBA)’s held for cadres. PMBA is an effort to prevent Stunting that is intended to provide cadres with knowledge, skills and tools that support mothers in improving optimal feeding practices for their babies and children.